2021
DOI: 10.3390/ijms222313147
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cigarette Smoking on the Expression of Oxidative Stress-Related Genes in Cumulus Cells Retrieved from Healthy Women Undergoing IVF

Abstract: The female reproductive system represents a sensitive target of the harmful effects of cigarette smoke, with folliculogenesis as one of the ovarian processes most affected by this exposure. The aim of this study was to analyze the impact of tobacco smoking on expression of oxidative stress-related genes in cumulus cells (CCs) from smoking and non-smoking women undergoing IVF techniques. Real time PCR technology was used to analyze the gene expression profile of 88 oxidative stress genes enclosed in a 96-well p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 78 publications
(100 reference statements)
1
13
0
Order By: Relevance
“…A fatty-acid-enriched diet increases the levels of the different hormones, such as FSH and LH, involved in the hypothalamic–pituitary–adrenal (HPA) axis, but also the concentration of ROS produced in the ovary and all stages of follicular growth, contributing to manifestation of oxidative stress. The relationship between oxidative stress and reproductive performance has been thoroughly studied [ 10 , 21 , 22 ], underlining that severe oxidative stress can concretely compromise follicular and ovarian development [ 37 ], and as a consequence, a balance of free radicals in the ovary is of vital importance. It has been demonstrated that due to high lipid levels, following ROS-induced lipid peroxidation in the ovaries of obese women, consequent oocyte apoptosis could be a contributing factor to significant follicular damage [ 38 ], negatively affecting ovarian function and female reproductive potential [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A fatty-acid-enriched diet increases the levels of the different hormones, such as FSH and LH, involved in the hypothalamic–pituitary–adrenal (HPA) axis, but also the concentration of ROS produced in the ovary and all stages of follicular growth, contributing to manifestation of oxidative stress. The relationship between oxidative stress and reproductive performance has been thoroughly studied [ 10 , 21 , 22 ], underlining that severe oxidative stress can concretely compromise follicular and ovarian development [ 37 ], and as a consequence, a balance of free radicals in the ovary is of vital importance. It has been demonstrated that due to high lipid levels, following ROS-induced lipid peroxidation in the ovaries of obese women, consequent oocyte apoptosis could be a contributing factor to significant follicular damage [ 38 ], negatively affecting ovarian function and female reproductive potential [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Granulosa cells not only provide various energetic substrates necessary for the nourishment of the oocyte, but also have a fundamental role in the formation of corpus luteum (CL), making them indispensable for the quality of the oocyte and embryo [ 8 ]. There are many factors related to the individual’s lifestyle that are able to negatively affect female fertility, such as high consumption of caffeine and alcohol, competitive sports, stress, cigarette smoking, chronic exposure to environmental pollutants and improper eating habits [ 10 , 11 , 12 , 13 ]. There is accumulating evidence that non-modifiable risk factors, such as genetic mechanisms and old age, are involved in the onset of infertility [see 1 for an extensive review].…”
Section: Introductionmentioning
confidence: 99%
“…Smoking in women of reproductive age is known to severely impact the ovaries and reproductive cells such as oocytes [ 6 ] and CCs [ 10 ] and potentially carry a risk for premature menopause, premature birth, abnormal fetal growth, low birth weight, and miscarriage [ 17 ]. As we previously described [ 10 ], several differentially expressed key genes related primarily to OS were identified in CCs following chronic exposure to cigarette smoke, suggesting a lower antioxidant capacity in CCs of smoking versus non-smoking women.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure used for the CCs isolation from COCs is the same as previously described in our study [ 10 ]. Briefly, the removal of CCs from COCs was aided with the exposure of COCs to hyaluronidase solution (HYASE-10XTM, Vitrolife, Goteborg, Sweden).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation